"Esculpir em argila": Albert Camus uma estética da existência - Silva, Gabriel Ferreira da (2009)
The present study aims to reveal the existential analysis undertaken by Albert Camus in sight of the constitution, in his thought, of an éthos that corresponds to the therms of the human demand for sense that is recognized as frustrated. Since his essay Le Mythe de Sisyphe posits as its fundamental problem the suicide as a possible action originated from the question for the sense of the existence, we must follow the development of the camusian construction of his anthropological discourse which has as its centre the notion of Passion in its three expressions -, as well as on the human condition that shows itself as opposite to the complete achievement of the human desire, featuring human experience as Absurd. Therefore, the question for the legitimacy of the suicide becomes even more radical. However, the distinguishing mark of the camusian thought is exactly the disbelief towards the human condition but an affirmation of the human desire for sense. Thus, after the invalidation of the suicide as a correlative práxis to the observation of the existential absurdity, it is necessary to develop an ethos of simultaneously confrontation of the human condition based on a deep acceptance of the Passion. Therefore, we follow the analysis of the three types or figures that express such attitude towards that one which, for Camus, properly embodies all the demands and limits of human Revolt: The Artist-Creator whose actions identifies fully with the revolted one s in the task of assynthotically modeling his existential experience intending to correct, within its own limits, the absurd condition, making the proposed camusian éthos for excelence an authentic aesthetic of the existence